Contribution to the knowledge of sweet molluscs of veterinary medical importance in Villa Clara, Cuba - Armiñana García, Rafael (2020)
The research is based on a malacological survey of freshwater molluscs of veterinary medical importance present in the Villa Clara province, Cuba. Methods associated with socio-cultural research were combined with methods and techniques used in laboratory and field work. In this sense, methods of the theoretical level (historical-logical, analytical-synthetic, and inductive-deductive) and empirical level (the survey, interview and documentary analysis) were used. The methodology allowed to verify the existing deficiencies on the knowledge of the freshwater aquatic molluscs species of medical importance. The collection of freshwater molluscs was carried out manually, using a hand strainer with a 1 mm mesh opening and a 2 m long handle for 10 minutes in the water bodies. The novel aspect of this research is that students and teachers from different Urban Basic Secondary Schools (ESBU) of several municipalities in the province of Villa Clara, Cuba were linked, and a system of workshops was proposed to contribute to the dissemination of these molluscs, from the educational project of the school.